A pragmatic randomised controlled trial of the Welsh National Exercise Referral Scheme: protocol for trial and integrated economic and process evaluation - Hale Janine; Ud Din Nafees; Williams Nefyn; Linck Pat; Edwards Rhiannon; Moore Graham; Raisanen Larry; Murphy Simon; Roberts Chris; McNaish Elaine; Moore Laurence (BMC, 2010)
Abstract Background The benefits to health of a physically active lifestyle are well established and there is evidence that a sedentary lifestyle plays a significant role in the onset and progression of chronic disease. Despite a recognised need for effective public health interventions encouraging sedentary people with a medical condition to become more active, there are few rigorous evaluations of their effectiveness. Following NICE guidance, the Welsh national exercise referral scheme was implemented within the context of a pragmatic randomised controlled trial. Methods/Design The randomised controlled trial, with nested economic and process evaluations, recruited 2,104 inactive men and women aged 16+ with coronary heart disease (CHD) risk factors and/or mild to moderate depression, anxiety or stress. Participants were recruited from 12 local health boards in Wales and referred directly by health professionals working in a range of health care settings. Consenting participants were randomised to either a 16 week tailored exercise programme run by qualified exercise professionals at community sports centres (intervention), or received an information booklet on physical activity (control). A range of validated measures assessing physical activity, mental health, psycho-social processes and health economics were administered at 6 and 12 months, with the primary 12 month outcome measure being 7 day Physical Activity Recall. The process evaluation explored factors determining the effectiveness or otherwise of the scheme, whilst the economic evaluation determined the relative cost-effectiveness of the scheme in terms of public spending. Discussion Evaluation of such a large scale national public health intervention presents methodological challenges in terms of trial design and implementation. This study was facilitated by early collaboration with social research and policy colleagues to develop a rigorous design which included an innovative approach to patient referral and trial recruitment, a comprehensive process evaluation examining intervention delivery and an integrated economic evaluation. This will allow a unique insight into the feasibility, effectiveness and cost effectiveness of a national exercise referral scheme for participants with CHD risk factors or mild to moderate anxiety, depression, or stress and provides a potential model for future policy evaluations. Trial registration Current Controlled Trials ISRCTN47680448